PS 13-17 APOPTOSIS INHIBITOR OF MACROPHAGE ACTIVATES INFLAMMATORY RESPONSE AFTER ACUTE MYOCARDIAL INFARCTION. (September 2016) - Nishikido, Toshiyuki; Oyama, Junichi; Tanaka, Atsushi; Shiraki, Aya; Komoda, Hiroshi; Node, Koichi
Abstract : Objective: The persistent inflammation response after myocardial infarction increases myocardial injury, and causes heart failure due to cardiac dysfunction and remodeling. Toll-like receptors (TLR)-4 was activated by the recognition of not only pathogen-associated molecular patterns but also endogenous ligands and it serves as proinflammatory function in circumstances involving myocardial tissue injury. Whereas, it was reported the apoptosis inhibitor of macrophage (AIM) provoke an efflux of saturated free fatty acid (FFA), one of the TLR4 ligands, due to lipolysis, which causes the chronic inflammation via TLR-4 pathway in adipose tissue. This study investigated the hypothesis that AIM activates a proinflammatory response after myocardial infarction. Design and Method: The ligation of the left anterior descending coronary artery to induced myocardial infarction was performed on both AIM-deficient(AIM−/−) mice and wild type (WT) mice. After 3 days, the inflammation responses were assessed in TLR-4/NFkB activation pathway. And infarct size/area-at-risk was measured by staining with Evans blue and triphenyltetrazolium chloride. In addition, the left ventricular remodeling was examined after 28 days. Results: AIM−/− mice showed significantly smaller infarct size compared with WT mice given similar area at risk (20.8 ± 0.6% vs. 27.8 ± 1.9%, p = 0.02). In AIM−/− mice with reduction of plasma FFA, IRAK4 and NFkB activity were decreased on myocardium (p = 0.02, 0.03 vs. WT, respectively). Moreover, there was the reduction of myeloperoxidase activity and iNOS in the inflammation response (p < 0.01, p = 0.03, respectively). We found that the NFkB DNA-binding activation via TLR-4, neutrophil infiltration, and inflammatory mediator were decreased in AIM−/− mice compared with WT mice after 3days. And, the heart weight to body weight ratio, myocardial fibrosis of AIM−/− mice were decreased, and a survival rate improved after 28 days (p < 0.01). Conclusions: AIM−/− mice demonstrated less inflammation response and smaller infarction size after myocardial infarction, suggesting AIM may activate a proinflammatory of TLR-4 after myocardial infarction.